1989
DOI: 10.1111/j.1751-1097.1989.tb02902.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and Fluorescence Quenching of Tyrosine in Lima Bean Trypsin/Chymotrypsin Inhibitor and Model Peptides

Abstract: The effects of citrate ion concentration and pH on the optical spectra and fluorescence decay have been measured for several tyrosine model compounds and lima bean trypsin/chymotrypsin inhibitor, a protein containing one tyrosine at position 69 and seven disulfides but no tryptophan, in order to determine the location and environment of Tyr 69. Tyrosine in the protein is protected from citrate collisional quenching, as indicated by the dynamic quenching constant 9 to 15 times smaller than those for the model p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…1 ). The absorption maxima were consistent with relevant examples from the literature [ 11 , 16 ]. The fluorescence emission maxima were 9 nm higher than a literature example (Leu-Tyr-Leu), probably as a result of differences in the conditions under which the measurements were made.…”
Section: Resultssupporting
confidence: 89%
“…1 ). The absorption maxima were consistent with relevant examples from the literature [ 11 , 16 ]. The fluorescence emission maxima were 9 nm higher than a literature example (Leu-Tyr-Leu), probably as a result of differences in the conditions under which the measurements were made.…”
Section: Resultssupporting
confidence: 89%
“…It is known from long ago [27] that tyrosine residue free in solution (pK a 10.6) or in peptides and proteins (pK a 9.6–10.4) [28] exhibits pK a due to ionization of the tyrosine phenolic hydroxyl. The latter was shown to depend on protein environment [23], and may vary from 9.6 to 10.4 due to interaction with protein interior.…”
Section: Resultsmentioning
confidence: 99%
“…The single tyrosine in LBTI has an abnormally high of > 11.5, most likely due to interactions with the protein. (173) Citrate fluorescence quenching studies of LBTI showed complex behavior. Based on simplifying assumptions, the quenching data also suggest that the tyrosine residue is shielded from solvent.…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…Based on simplifying assumptions, the quenching data also suggest that the tyrosine residue is shielded from solvent. (173) 1.5.1.5. Other Proteins l.5.l.5a.…”
Section: Protease Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation